Total mesorectal excision with or without lateral pelvic lymph node dissection in rectal cancer with special reference to japanese guidelines: a comparative study - By Ahmed Mohamed Abdelaal Hassan; Osama Refaie Mohamed (2022)
(3jeKd SQWGf GdeSJbje GdSHH GdQFjSj GdKGdK ddhaGI aj LejY CfMGA GdYGde eY MOhK RjGOI eWQOI(B. (3dG JRGd aYGdjI GSJFUGd GdYbO GddeaGhjI GdhMTjI HGdMhV ehVhkYG eKjkQG ddLOd(B. (3cGf GdgOa ef gPg GdOQGSI gh Jbjje MOhK GQJLGY ehVYj dSQWGf GdeSJbje Hjf GdeQVi GdPjf NVYhG dGSJFUGd cdj ddeSJbje eY Ch HOhf GSJFUGd GdYbO GddeaGhjI GdhMTjI HGdMhV aj SQWGf GdeSJbje CLQjJ GdOQGSI Ydi (B46 (3eQjVG NVYhG dYedjGJ LQGMjI deQVi SQWGf GdLRA GdGSad ef GdeSJbje aj bSe LQGMI Gdbhdhf hGdeSJbje HcdjI GdWH bUQ GdYjfj , Je Jbjje GdeQVi bHd GdLQGMI (B((3CNP GdJGQjN GdeQVj hGdaMU GdGcdjfjcj, GdaMU GdTQLj, efXGQ Gdbhdhf hGNP YjfI ef GdhQe Yf WQjb efXGQ Gdbhdhf, Yed CTYI HGdQfjf GdeZfGWjSj Ydj GdMhV hYed GTYI ebWYjI Ydj GdUOQ hGdHWf hGdMhV(B) (3Je JbSje GdeQVi Edi eLehYJjf, GdeLehYI C(B: (3NVYhG dGSJFUGd cdj ddeSJbje hGdeSGjbG GNO YdGL GTYGYj hcjeGhj bHd GdYedjI, GdeLehYI H(B: (3NVYhG dGSJFUGd cdj ddeSJbje hGdeSGQjbG hGSJFUGd GdYbO GddjeaGhjI GdhMTjI HGdMhV eY GdMaGX Ydi GdYUH GdeZPjI ddLgGR GdHhdj hGdJfGSdj(B. (3Je Yed JMdjd GCfSLI ddYjfGJ GdLQGMjI(B. (3hJe ebGQfI hbJ GdYedjI habOGf GdOeGKfG GdYedjI Hjf GdeLLehYJjf hJeJ eJGHYI GdeQVi dMOhK GQJLY GdhQe hGNJdGd hXjaj aj GdLgGR GdHhdj hGdJfGSdj (B. (3cGfJ fSHI GdGQLGY GdehVYj ddQhe GdSQWGfj HGdeSJbje CYdi bdjdkG aj GdeLehYI C (B(8.7(3%(B) (3ef GdeLehYI H (B(4.3(3%(B) (3hdcfgG djSJ PGJ OdGdI EMUGFjI hcGfJ fSHI GdGQJLGY GdHYjO ddQhe GdSQWGfj HGdeSJbje aj GdeLehYI C (B(8.7(3%(B) (3haj GdeLehYI H (B(13(3%(B) (3hdcfgG djSJ PGJ OdGdI EMUGFjI(B. (3cGf GdVYa GdHhdj hGdLfSj CYdi aj GdeLehYI H (B(26.1(3%(B) (3ebGQfI HGdeLehYI C (B(21.7(3%(B) (3, hdcf de PGJ OdGdI EMUGFjI(B. (3hcGf hbJ GdYedjI habOGf GdOe GKfGA GdYedjI CYdj aj GdeLehYI H GdJj NVYJ dGSJFUGd cdj ddeSJbje hGdeSGQjbG hGSJFUGd GdYbO GddjeaGhjI GdhMTjI hcGf PGJ OdGdI EMUGFjI GSJfJLfG ef GdOQGSI Gf GdGSJFUGd Gdcdj ddeSJbje eY GSJFUGd GdYbO GddeaGhjI GdhMTjI HGdMhV de jcf eQJHkWG HGfNaGV eYJO Hg EMUGFkjG aj MOhK GQJLGY ehVYj ddhQe GdSQWGfj HGdeSJbje ,hdcfg bdd ef eYOd MOhK GQJLGY ehVYj HfSHI eeGKdI GMUGFjG ddYdGL GdETYGYj hGdcjejGhj bHd GdLQGMI(B. (3ceG Cf GSJFUGd GdYbO GddeaGhjI GdhMTjI HGdMhV eY GdMaGX Ydi GdYUH GdeZPjI ddLgGR GdHhdj hGdJfGSdj dG jSHH GNJdGd hXjaj LfSj hHhdj Pj OdGdI EMUGFjI(B. (3cGf hbJ GdYedjI habOGf GdOe GKfGA GdYedjI CYdj aj GdeLehYI GdJj NVYJ dGSJFUGd cdj ddeSJbje hGdeSGQjbG hGSJFUGd GdYbO GddjeaGhjI GdhMTjI hcGf PGJ OdGdI EMUGFjIs
Thesis (Ph.D)-Cairo University,2022.
Bibliography: p. 85-105.
Keywords: Rectal Cancer; Total Mesorectal Excision